2010
DOI: 10.3324/haematol.2010.026104
|View full text |Cite
|
Sign up to set email alerts
|

Weekly rituximab followed by monthly rituximab treatment for steroid-refractory chronic graft-versus-host disease: results from a prospective, multicenter, phase II study

Abstract: BackgroundSince it was suggested that B cells play a role in the pathogenesis of chronic graft-versus-host disease, rituximab, an anti-CD20 monoclonal antibody targeting B cells, has been shown to be effective in steroid-refractory, chronic graft-versus-host disease. However, most of the data were from small numbers of patients or retrospective analyses. We, therefore, conducted a multicenter phase II study to confirm the efficacy of this treatment strategy that targets B cells. Design and MethodsWe diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
4
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 28 publications
(66 reference statements)
0
49
4
5
Order By: Relevance
“…Extended dose of rituximab is known to potentiate its clinical response [10,11]. Our recent study also suggested that additional monthly rituximab could improve long-term outcomes in AE nonresponsive to first-line immunotherapies [8].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 95%
See 1 more Smart Citation
“…Extended dose of rituximab is known to potentiate its clinical response [10,11]. Our recent study also suggested that additional monthly rituximab could improve long-term outcomes in AE nonresponsive to first-line immunotherapies [8].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 95%
“…Patients who switched treatment regimens from monthly rituximab maintenance to tocilizumab owing to a lack of clinical improvement were included in the tocilizumab group. In the additional rituximab group, rituximab was administrated in 1-month intervals, beginning at 1 month after the last infusion of weekly rituximab, with the same dosage (375 mg/m 2 ) [10].…”
Section: Treatmentsmentioning
confidence: 99%
“…These agents can be used either as a part of the conditioning before HSCT or as a treatment for GvHD, a condition associated with increased risk for TB. There are case reports of TB in patients given alemtuzumab as part of the conditioning therapy [131], and one suspected but unproven case of TB associated with rituximab given for chronic GvHD [132]. Although there are few data in HSCT, most of these agents have been associated with an increased risk for TB in other patient populations and may pose an increased risk in the HSCT population as well [133,134].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Although several studies have suggested an effect on cGvHD in the skin, 66,[95][96][97][98] no convincing effect on BO has been established. 66,67 …”
Section: Rituximabmentioning
confidence: 99%